2020
DOI: 10.1371/journal.pone.0231637
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of Mycobacterium Tuberculosis in metropolitan Harare, Zimbabwe

Abstract: Introduction The contribution of high tuberculosis (TB) transmission pockets in propagating area-wide transmission has not been adequately described in Zimbabwe. This study aimed to describe the presence of hotspot transmission of TB cases in Harare city from 2011 to 2012 using geospatial techniques. Methods Anonymised TB patient data stored in an electronic database at Harare City Health department was analysed using geospatial methods. Confirmed TB cases were mapped using geographic information system (GIS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
(45 reference statements)
3
13
1
1
Order By: Relevance
“…The occurrence of TB hotspots and clusters in these areas may be associated with high population resulting in overcrowding hence ease transmission of the disease. These results are similar to findings by Chirenda [ 14 ] who found that TB hotspots and clusters are common in urban areas due to large populations and inadequate health care services. Consistently across the four years, and especially in 2017, the districts along the Great Dyke exhibited TB hotspots.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The occurrence of TB hotspots and clusters in these areas may be associated with high population resulting in overcrowding hence ease transmission of the disease. These results are similar to findings by Chirenda [ 14 ] who found that TB hotspots and clusters are common in urban areas due to large populations and inadequate health care services. Consistently across the four years, and especially in 2017, the districts along the Great Dyke exhibited TB hotspots.…”
Section: Discussionsupporting
confidence: 91%
“…These studies have generated important information about the distribution of the disease and its transmission patterns. However, the major limitation of these studies is that they are biased towards smaller spatial scales such as a single urban area over short temporal durations [ 14 , 26 ]. By focussing on smaller spatial scales, these studies fail to capture the spatial pattern of TB at a spatial scale that is relevant for TB programming, for example district scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar pattern of findings were obtained in Zhang et al's study suggesting that discrepancies between the current and desired conditions within an organization overshadowed the high change commitment for programs [26]. Notwithstanding, our study had limited time and resources therefore was conducted at one-point in time as compared to the aforementioned previous study that measured readiness at the pre-adoption, preimplementation and post-implementation stages of the program [26].…”
Section: Change Commitmentsupporting
confidence: 82%
“…Anselin’s Local Moran’s I (ALMI ) identifies High-High clusters, Low-Low clusters, and spatial outliers (High-Low and Low-High) [ 47 ]. High-High clusters indicate areas with a high TB incidence rates surrounded by areas with similarly high TB rates, while Low-Low clusters designate areas with low TB incidence rates surrounded by areas with low rates; High-Low outliers specifies areas with high TB incidence rates surrounded by areas with low rates, while Low-High outliers indicate the opposite, i.e.…”
Section: Methodsmentioning
confidence: 99%